Literasi Digital Keamanan Siber pada Remaja menghadapi Social Engineering - Effendy, M. Yusuf; Oktiani, Hestin (P3M STISIPOL Dharma Wacana Metro, 2024)
Personal data protection and security in information transactions in the digital era are very important. The development of digital technology has given birth to various cybercrimes. Awareness of cyber security is the key to protecting yourself from social engineering related to several key security elements, namely passwords and Two-Factor Authentication (2FA). Teenagers (Gen Z) are the age group with the highest penetration on internet/cyber media, meaning that teenagers are also at greatest risk of experiencing cybercrime. Based on the results of the study, out of 100 respondents selected with the criteria of having email, social media, internet banking, and e-commerce accounts, teenagers as the largest users of internet media in general (70%) are aware of the existence of social engineering as a cybercrime, but most (54%) do not yet have knowledge about 2-factor authentication (2FA) as a way to protect personal data. Knowledge about cybercrime has not been accompanied by a high awareness to carry out good protection procedures against cybercrime, only 38%-42% of teenagers do it. In addition, the digital literacy they have is also not adequate to deal with cybercrime attacks, especially social engineering. Teenagers’ digital literacy in dealing with cybercrime is still inadequate and needs to be improved. Teenagers’ knowledge of 2-factor authentication (2FA) and the use of strong passwords and their awareness of the importance of taking cyber security measures are ways to deal with cybercrime attacks. More intensive training is needed on digital literacy, especially on cyber security in dealing with social engineering cybercrime.